Grammatical Errors: An Analysis in Speaking Produced by EFL Undergraduate Students - Safrida Safrida; Usman Kasim (Universitas Syiah Kuala, 2016)
Many EFL learners produce many errors in their speaking regarding grammatical aspect. The present study aims to analyze the most dominant errors and causes of errors committed by the third semester students of Syiah Kuala University on their speaking in Indonesia. The data were collected from eight by asking them to produce short story about their most memorable experience orally for 5-8 minutes. Furthermore, the writer followed the error analysis procedures to analyze the data. Moreover, the errors were classified into surface strategy taxonomy as proposed by Dulay et.al. (1982). The result shows that the most dominant errors were omission (55%) followed by misformation (29%), addition (13%), and misordering (3%). The current study investigated that the causes of errors were intra-lingual and inter-lingual interference. Meanwhile, intra-lingual interference was considered as the major cause of the students’ errors. In conclusion, the students still have a serious problem in term of grammatical aspect, especially omission of noun inflections and irregular past tenses, and misformation of auxiliaries. It is suggested that the lecturers and the students do some efforts to reduce the grammatical errors in speaking, such as grammar drill and error correction.